Wing Pattern Diversity in the Papilionid Butterflies (Rhopalocera-Papilionidae) - Nur Azizuhamizah, Idris (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study describes and compares the diverse variety of dorsal and ventral wing patterns and colouration in the family Papilionidae. Twenty-six Bornean Papilionid species from 250 specimens deposited in the Zoology Museum of Faculty of Resource Sciences and Technology, UNIMAS were examined and the pattern elements of the nymphalid groundplan were illustrated and labelled in colour. The Papilionids show diverse wing patterns and colourations. The dorsal surface comprised a smaller number of discernible patterns elements than the ventral surface, and so are the hindwings which have less recognizable pattern elements than the forewings. The nymphalid groundplan pattern elements commonly displayed by the subfamily Papilionini are paraforcal element (i), submarginal element (j) and trailing bands. Several special patterns such as dependent patterns and sparse pattern are also displayed. The characteristic of wing patterns can be used to track the relation between species due to the homology of the wing patterns. Species that belongs to the same tribe are clustered together in UPGMA with lower similarity distance. The enlargement, dislocation and fusion of patterns elements of nymphalid groundplan in the Papilionidae are also discussed.